Memory T cell responses in influenza A infection and vaccination in humans - Chui, C (2012)
Protective immunity against influenza virus infection is believed to be mediated by neutralising antibodies. Despite substantial evidence in animal models which suggests critical roles for T cells in viral clearance, the precise role of cellular immunity in human influenza immunity remains uncertain. The first aim of this project was to determine cellular immune responses in seronegative human volunteers following nasal challenge with live seasonal H3N2 or H1N1 viruses. T cell responses before and during infection were mapped. A large increase in both breadth and magnitude in influenza-specific CD4+ T cell responses was seen in the blood by day 7, when virus was completely cleared from nasal samples and serum antibodies were still undetectable. These acutely expanded T cells were shown to be highly activated (CD38+) and proliferating (Ki-67+). Pre-existing CD4+ T cells, but not CD8+, specific to internal proteins nucleoprotein and matrix proteins, were associated with lower virus shedding and less severe illness. These influenza-specific T cells also responded to A/California/07/2009 (H1N1) peptides, were able to kill antigen-loaded autologous B cell lines in vitro and were polyfunctional in cytokine production. The second aim was to assess the cellular immune responses to unadjuvanted, inactivated seasonal and pandemic A/California/07/2009 (H1N1) influenza vaccines. 151 healthy adult volunteers were vaccinated: modest influenza-specific T cell responses were induced, and specific responses to HA and NA peptide pools were found to be mediated by CD4+ T cells. Activated and proliferating cells induced during vaccination were found to be of a central memory phenotype. Lastly, I explored the link between antibody production and CD4+ T cells. The ability of CXCR5+ CD4+ T cells from peripheral blood to support antibody production was examined and antigen-specific CD4+ T cells with helper functions could be found in the peripheral blood of healthy volunteers with memory influenza-specific T cells. This thesis suggests that influenzaspecific CD4+ T cells have an important role in limiting the severity of influenza infection in the absence of specific antibody responses through a number of mechanisms. This work provides information on how cellular immunity can be targeted in conferring broad protection against different subtypes of influenza A viruses in the development of universal flu vaccine.